Integrating Local Wisdom into Entrepreneurship Education for Sustainable Tourism in Pulo Aceh, Indonesia - Rizka, Rizka; Anwar, Anwar; Nasir, Nasir; Sinala, Ahmad; Imam, Gunanjar; Faridy, Najihatul; Bangkara, B.M.A.S. Anaconda (SCAD Independent, 2025)
Pulo Aceh is rich in natural resources and local wisdom with high potential to become a tourist destination. However, community awareness of this potential is still low, encouraging us to find strategies to raise this awareness and develop entrepreneurial spirit among local students in the tourism industry. A qualitative method with a descriptive analysis approach was employed. The data collection techniques included observations and interviews with school teachers and several local people of Pulo Aceh. The findings revealed that Pulo Aceh’s natural landscape and resources play an essential role in the development of Pulo Aceh’s tourism. For the sustainability purpose, the awareness and skills in tourism businesses should be built from a young age, specifically in the middle school and high school levels. The knowledge and skills can be integrated into a school subject and taught through tourism business-related materials. Seven strategies were also proposed to build students’ entrepreneurial spirit, namely 1) linking lesson material to real life, 2) using technology, 3) applying project-based learning, 4) designing creative activities, 5) social involvement, 6) giving appreciation to students, 7) material flexibility and adequate information about future careers in the tourism industry. Through these strategies, it is expected that these young entrepreneurs are born and improve the region’s economy